Evaluation of imatinib mesylate in the treatment of pulmonary arterial hypertension. (January 2010) - Chhina, Mantej K; Nargues, Weir; Grant, Geraldine M; Nathan, Steven D
Imatinib mesylate is a small molecule inhibitor that selectively inhibits the PDGF receptor kinase as well the cKIT and Abl kinases, among other targets. Various studies have implicated the PDGF pathway in the pathogenesis of pulmonary arterial hypertension (PAH). Inhibition with imatinib mesylate has shown efficacy in human case reports and experimental models of PAH. Results from a Phase II trial of imatinib mesylate in PAH did not meet the primary end point but showed improvement in several secondary end points and in a subgroup analysis. As suggested by this study as well as a few case reports, imatinib may be effective in a subset of patients with more severe disease. However, this remains to be further validated through a Phase III study, which is already underway. In conclusion, it appears that imatinib mesylate may hold promise as an adjunct drug in PAH therapy, especially since it is directed at a pathway not previously targeted.